Effects of feedstock ratio and organic loading rate on the anaerobic mesophilic co-digestion of rice straw and cow manure. (August 2015) - Li, Dong; Liu, Shengchu; Mi, Li; Li, Zhidong; Yuan, Yuexiang; Yan, Zhiying; Liu, Xiaofeng
Graphical abstract: Highlights: The optimal ratio of rice straw to cow manure was 1:1 based on volatile solids. Stable biogas production was obtained at an organic loading rate of 3–6 kg VS/(m 3 d). The overloaded system was inhibited by volatile fatty acids rather than ammonia. The recommended organic loading rate for the co-digestion is 6 kg VS/(m 3 d). Digestion system foaming was observed at an organic loading rate ⩾8 kg VS/(m 3 d). Abstract: In order to investigate the effects of feedstock ratio and organic loading rate (OLR) on the anaerobic mesophilic co-digestion of rice straw (RS) and cow manure (CM), batch tests (2.5 L) were carried out at volatile solid (VS) ratios of 0:1, 1:2, 1:1, 2:1, and 1:0 (RS/CM), and continuous bench experiments (40 L) were carried out at OLRs of 3.0, 3.6, 4.2, 4.8, 6.0, 8.0, and 12.0 kg VS/(m 3 d) with optimal VS ratio. The optimal VS ratio was found to be 1:1. Stable and efficient co-digestion with average specific biogas production of 383.5 L/kg VS and volumetric biogas production rate of 2.30 m 3 /(m 3 d) was obtained at an OLR of 6 kg VS/(m 3 d). Anaerobic co-digestion was severely inhibited by the accumulation of volatile fatty acids instead of ammonia when the OLR was 12 kg VS/(m 3 d). Further, significant foaming was observed at OLR ⩾ 8 kg VS/(m 3 d).